2020
DOI: 10.1021/acsami.9b20500
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Room-Temperature Phosphorescence Obtained from Water-Dispersible Carbon Dot-Based Composite Materials

Abstract: Room-temperature phosphorescence (RTP) materials are desirable in chemical sensing because of their long emission lifetime and they are free from background autofluorescence. Nevertheless, the achievement of RTP in aqueous solution is still a highly challenging task. Herein, a molten salt method to prepare carbon dot (CD)-based RTP materials is presented by direct calcination of carbon sources in the presence of inorganic salts. The resultant CD composites (CDs@MP) exhibit bright RTP with a quantum yield of 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 63 publications
(123 reference statements)
1
98
1
Order By: Relevance
“…[2a,3] The metal-doped materials with long lifetime generally have a high cost, cytotoxicity and low stability. [4] Meanwhile, the organic afterglow materials are less efficient because of their low lightfastness. [2b,5] These materials also often demand complicated synthesis procedures (high temperature, long duration, strong, redox material).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2a,3] The metal-doped materials with long lifetime generally have a high cost, cytotoxicity and low stability. [4] Meanwhile, the organic afterglow materials are less efficient because of their low lightfastness. [2b,5] These materials also often demand complicated synthesis procedures (high temperature, long duration, strong, redox material).…”
Section: Introductionmentioning
confidence: 99%
“…However, long lifetime materials have several limitations [2a,3] . The metal‐doped materials with long lifetime generally have a high cost, cytotoxicity and low stability [4] . Meanwhile, the organic afterglow materials are less efficient because of their low lightfastness [2b,5] .…”
Section: Introductionmentioning
confidence: 99%
“…The proposed aggregation-induced RTP mechanism was supported by TEM imaging in which randomly oriented CD aggregates were observed (Figure 8(i)). Another example was reported by Wang et al in 2020, who have found that enhancing ethanol fraction in an acidic CD dispersion higher than 30% can also trigger the appearance of yellow RTP [52]. In this case, enhancing the ethanol fraction in the mixture first led to the formation of CDs@MS nanocomposites which underwent further aggregation and gave rise to bright yellow RTP in the resulting solution (Figure 8(m)).…”
Section: Aggregation-induced Afterglow Luminescence Aggregation-induced Emission (Aie) Is An Interesting Photophysical Phenomenon Reportementioning
confidence: 69%
“…Despite the attractiveness, the use of MS in the preparation of CD-based afterglow nanocomposites is hindered by the hygroscopic nature of the used MS, which enables the weak photoluminescence stability of the resultant CDs@MS nanocomposites. This concern can be partially addressed by doping MgCl 2 and KH 2 PO 4 into the MS in the carbonization synthesis of CDs, as supported by their follow-up work [52]. Owing to the poor solubility of Mg-PO 4 salts in water, the tolerance of the afterglow luminescence toward water has been considerably improved, even leading to the observation of a bright long-lived yellow RTP in an aqueous solution of the resulting CD@MP after ceasing the UV excitation (Figures 5(b)-5(d)).…”
Section: Molten Salt Encapsulation Activation Molten Salt (Ms)mentioning
confidence: 99%
See 1 more Smart Citation